Factors Associated with the Incidence of Anemia in Students of Akbid Helvetia Pekanbaru in 2021 - Rika Istawati (JURNAL PROTEKSI KESEHATAN, 2021)
ABSTRACT WHO data states that the incidence of anemia in adolescent girls in Southeast Asia is 25-40%. Risk factors for anemia include breakfast habits, duration of menstruation, level of knowledge about anemia, nutritional status. The impact of high-risk anemia during pregnancy and childbirth is 43%, inhibits growth and development and reduces learning ability by 45.31%. The purpose of this study was to determine the factors associated with the incidence of anemia in students of Akbid Helvetia Pekanbaru. This type of research is quantitative with cross sectional design and chi-square test. The population of third year students at Akbid Helvetia Pekanbaru was 34 people using the total sampling technique. The instrument uses a questionnaire, easy touch digital hb, weight scales and stature meter. The results of statistical tests showed that there was no significant relationship between breakfast habits p-value 0.905, level of knowledge p-value 0.678 on anemia, there was a relationship between menstrual period p-value 0.001, nutritional status p-value 0.003 and anemia. It is expected that respondents can increase Hb levels and prevent anemia by consuming foods rich in iron, folic acid, vitamin B12 and vitamin C, and avoiding excessive caffeine.